Ascomycetes (Fungi: Ascomycota) of the Agua Blanca State Park, Macuspana, Tabasco, Mexico - Ávalos Lázaro, Abisag Antonieta; Rosique Gil, José Edmundo; Cappello García, Silvia; Villarruel Ordaz, José Luis (Instituto de Ecología, A.C., 2018)
Background and Aims: The diversity of the macroscopic ascomycetes currently known from the Agua Blanca State Park, Tabasco, is the result of several previous investigations of macromycetes at the state level. As there is no specific study on the ascomycetes of the aforementioned park, in this work the previous records were combined with the results of new explorations within this project.Methods: The Agua Blanca State Park is located in the western and northeastern region of the state of Tabasco, Mexico. Twenty eight explorations were carried out between December 2011 and July 2015. The material collected was deposited in the UJAT herbarium for its preservation and identification. Identification of the samples was carried out following the conventional mycological techniques.Key results: 129 specimens were revised, allowing for the determination of 22 species belonging to two classes, three orders, five families and eight genera. The genera Scutellinia and Rosellinia are reported for the first time for the state. The genus Xylaria is the most diverse with 10 species, while the genera Ophiocordyceps, Scutellinia, Hypoxylon and Rosellinia are the least diverse with one species each.Conclusions: Of the 22 species identified, 12(55%) were new records for Tabasco and 18(22%) were this for the study area, while 10(45%) of the species had previously been found in the state and 4(18%) in the reserve. Finally, this study shows a higher number of species evaluated compared to previous work.